Amyloid-beta peptide toxicity in the aged brain is a one-way journey into Alzheimer’s disease - Culley, Georgia; Henriques, Alexandre; Hardy, Delphine; Wojcinski, Alexandre; Chabert, Adrien; El Waly, Bilal; Poindron, Philippe; Callizot, Noelle (Frontiers in Aging Neuroscience, 2025)
Aging is the primary risk factor for Alzheimer’s disease (AD), and the aging brain shares many characteristics with the early stages of AD. This study investigates the interplay between aging and amyloid-beta (Aβ) induced pathology. We developed an AD-like in vivo model, using the stereotactic injection of Aβ1–42 oligomers into the hippocampi of aged mice. Cognitive impairments were assessed using a Y maze. Immunohistochemical and protein analyses were conducted to evaluate neuronal survival, synaptic function and number, levels of tau hyperphosphorylation, microglial activation, autophagy, and mitochondrial function. We compared baseline aging effects in young adult (3 months) and aged (16-18 months) healthy mice. We found that aged mice displayed significant deficits in working memory, synaptic density and neurogenesis, and an increased basal inflammation. In response to acute injury to the hippocampus with Aβ oligomer injection, aged mice suffered sustained deficits, including impaired cognitive function, further reduced neurogenesis and synaptic density, increased microglial activation, astrogliosis, mitochondrial stress, and lysosomal burden. Furthermore, in the weeks following injury, the aged mice show increased amyloid accumulation, microglial activation and phosphorylated tau propagation, expanding from the injection site to adjacent hippocampal regions. In contrast, the young adult mice exhibited only acute effects without long-term progression of pathology or neurodegeneration. We conclude that the aging brain environment increases susceptibility to an acute Aβ injury, creating fertile soil for the progression of AD, whereas younger brains are able to overcome this injury. The processes of aging should be considered as an integral factor in the development of the disease. Targeting aging mechanisms may provide new strategies for AD prevention and treatment, as well as for other neurodegenerative diseases.